2020
DOI: 10.1097/mej.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Application of decision rules on diagnosis and prognosis of renal colic: a systematic review and meta-analysis

Abstract: Renal colic is a prevalent emergency department presentation resulting from urolithiasis. Clinical decision rules for the diagnosis of urolithiasis were developed to help clinicians with better judgment. In this systematic review, we assessed the performance of prediction rules on urolithiasis diagnosis and prognosis. MEDLINE, Embase, Web of Science, and Scopus were searched for studies on the performance of a clinical decision tool for diagnosis or prognosis of urolithiasis. Performance and accuracy of the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…In 2018, Başeskioğlu et al designed the Osmangazi University Score, which used nausea, a history of stones, Cre, and hematuria [ 5 ]. In a meta-analysis that included the aforementioned scoring systems along with six others, Mirfazaelian et al found the STONE scoring system to be superior to others [ 1 , 19 - 22 ]. The same year, Fukuhara et al reported that the CHOKAAI score was superior to STONE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, Başeskioğlu et al designed the Osmangazi University Score, which used nausea, a history of stones, Cre, and hematuria [ 5 ]. In a meta-analysis that included the aforementioned scoring systems along with six others, Mirfazaelian et al found the STONE scoring system to be superior to others [ 1 , 19 - 22 ]. The same year, Fukuhara et al reported that the CHOKAAI score was superior to STONE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis is a common disease with a lifetime incidence of 12% and a high cost for healthcare worldwide [ 1 , 2 ]. Although ultrasonography (US) is the first-line diagnostic method in stone diagnosis, it is highly dependent on the attention and experience of the person performing it, and its sensitivity remains low, especially in detecting ureteral and kidney stones [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of current evidence A total of 21 publications addressed this question via different methods, including 8 retrospective studies, 7 prospective observational studies, 4 systematic reviews, and 2 RCTs (Table 2 in Supplement B). 2,6,12,15,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Only 1 study directly compared immediate CT to delayed CT in patients who were clinically improving in the EDand neither group had any alternative diagnoses considered lifethreatening. 28 "Alternative diagnoses" were not standardized and were not always clearly defined as dangerous, emergent, or urgent.…”
Section: 21mentioning
confidence: 99%
“…A total of 14 studies sought to develop and validate prediction rules with the goal of predicting the likelihood that a patient with flank pain has ureterolithiasis (Table 6 in Supplement B). 24,30,32,[48][49][50][51][52][53][54][55][56][57][58] Of the 14 studies included, 1 was a 2019 meta-analysis that sought to assess the performance of existing prediction rules. The STONE score and the CHOKAI score were most frequently evaluated.…”
Section: Summary Of Current Evidencementioning
confidence: 99%